ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø§Ù„Ù…ÙˆØ§Ø¯ ØºÙŠØ± Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ Ø¶ÙˆØ¡ Ù…Ø¯Ø®Ù„ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„ØªÙƒØ§Ù…Ù„ÙŠ Ù„Ù„Ù…ØØªÙˆÙ‰ ÙˆØ§Ù„Ù„ØºØ© Ø¨Ù…Ø¹Ù‡Ø¯ ÙˆØ§Ù„ÙŠ ØµØ§Ø¹Ø§ Ø¹Ø§Ø¨Ø± Ù„Ù„ØªØ±Ø¨ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙˆÙ†ÙˆØ±ÙˆÙƒÙˆ - Haryoto Haryo Haryo (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2023)
Wali Songo Ngabar Islamic Boarding School is one of the Islamic educational institutions in Indonesia that has great attention to Arabic. Arabic is used as the medium of instruction in teaching Islamic studies. TMI Grade Two students are beginners in this teaching, as they previously studied Islamic subject matter using Indonesian. And similar to this teaching, is teaching language according to the Content and Language Integrated Learning (CLIL) Approach, which assumes that teaching a foreign language is not enough just to teach in theory but must use it in teaching and learning activities. From that the researcher is motivated to do more research on the teaching of Arabic. provide a new discourse in teaching Arabic, especially in Indonesia. This study aims to explain the teaching of Arabic and its suitability with the characteristics of teaching foreign languages according to the CLIL approach. This research is a Case Study type Field Research with a Qualitative Approach and Descriptive Study Research Methodology. In collecting data using Documentation & Library Methods, Interviews, and Observations. For data analysis using interactive analysis method by Miles and Hubberman. The results of this study: First, teaching Islamic lessons through Arabic is teaching Arabic according to language teaching according to the CLIL approach in terms of 4 main principles, namely Content, Communication, Cognition, and Culture. Second, the purpose of this teaching is in accordance with CLIL, which is to improve students' foreign language skills. Third, learning activities are based on the Direct Method of Teaching Language, namely by using a foreign language directly and clearly, and using correct grammar.